IDO1 and TDO inhibitory evaluation of analogues of the marine pyrroloiminoquinone alkaloids: Wakayin and Tsitsikammamines. (15th May 2021) - Levy, Thomas; Marchand, Laura; Stroobant, Vincent; Pilotte, Luc; Van den Eynde, Benoît; Rodriguez, Frédéric; Delfourne, Evelyne
Graphical abstract: Highlights: Analogues of the marine alkaloid tsitsikammamines and wakayin have been prepared; Their capacity to inhibit hIDO1 and hTDO were evaluated on cell lines over expressing the enzymes. Docking experiments were realized in order to explain the results observed for the two better compounds. Abstract: Indoleamine 2, 3-dioxygenase (IDO1) and tryptophane 2, 3-dioxygenase (TDO) are two heme-containing enzymes which catalyze the conversion of tryptophan to N -formylkynurenine. Both enzymes are well establish therapeutic targets as important factors in the tumor immune evasion mechanism. A number of analogues of the marine pyrroloquinoline alkaloids tsitsikammamines or wakayin have been synthesized, two of them were synthesized using an original method to build the bispyrroloquinone framework. All the derivatives were evaluated in a cellular assay for their capacity to inhibit the enzymes. Six compounds have shown a significant potency on HEK 293-EBNA cell lines expressing hIDO1 or hTDO.